2021
DOI: 10.1002/prep.202100173
|View full text |Cite
|
Sign up to set email alerts
|

On the Question of the Energetic Performance of TKX‐50

Abstract: An analysis of the experimental data available to date shows that the explosive TKX‐50 has really high explosive performance characteristics, although not as outstanding as claimed previously, due to the overestimation of the enthalpy of formation. The obtained experimental data on the dependence of the detonation velocity on the density of TKX‐50 samples agree with the results of calculations, in which the experimentally determined enthalpy of formation 194.1 kJ mol−1 is used. The energetic performance of TKX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…As is known, CL-20 has been the most powerful non-nuclear energetic compound in practice so far. 64,65 Figure 11 further shows the similarity for the 10 molecules. Low scores in the similarity mean that the 10 molecules are highly different in the structures like the parent rings and the substituents.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As is known, CL-20 has been the most powerful non-nuclear energetic compound in practice so far. 64,65 Figure 11 further shows the similarity for the 10 molecules. Low scores in the similarity mean that the 10 molecules are highly different in the structures like the parent rings and the substituents.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…In particular, the top three molecules present comparable or higher detonation velocities than complicatedly caged CL-20 (9.455 km/s), along with a lower SA (SA of CL-20: 5.44). As is known, CL-20 has been the most powerful non-nuclear energetic compound in practice so far. , …”
Section: Resultsmentioning
confidence: 99%
“…Finally, in order to assess the versatility of Cu 1.8 S in laser ignition, promising second explosives such as most powerful 2,4,6,8,10,12‐(hexanitrohexaaza) cyclododecane (CL‐20), [ 31 ] high‐energy but insensitive dihydroxylammonium 5,5′‐bistetrazole‐1,1′‐diolate (TXK‐50), [ 32 ] 4,4′,5,5′‐Tetranitro‐1 H,1′H‐[2,2′‐biimidazole]‐1,1′‐diamine (DATNBI), [ 33 ] and most insensitive explosives 1,3,5‐triamino‐2,4,6‐trinitrobenzene (TATB) [ 34 ] were coated with 5 wt% Cu 1.8 S through similar solvent evaporation methods as in case of AP@Cu 1.8 S microsuperlattices and then subjected to laser illumination at 1064 nm. As expected, it is found that CL‐20 ( Figure a and S10, Supporting Information), TKX‐50 (Figure 7b and S11, Supporting Information), and DATNBI (Figure 7c and S12, Supporting Information) cannot be ignited at all unless in the presence of Cu 1.8 S, Interestingly, the color of inner flame was bright white, while the color of outer flame was faint green, this phenomenon is ascribed to the flame color reaction of Cu[I] derived from Cu 1.8 S NCs.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent publication, Sinditskii et al reported an experimentally determined enthalpy of formation for TKX-50 of + 194.1 kJ mol À 1 and a calculated detonation velocity at a density of 1.8 g cm À 3 of 9037 m s À 1 [5]. Graswald et al reported a measured detonation velocity for a TKX-50/wax/ graphite formulation (94.5/4.5/1) of 9020 m s À 1 at a formulation density of 1.776 g cm À 3 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication, Sinditskii et al. reported an experimentally determined enthalpy of formation for TKX‐50 of +194.1 kJ mol −1 and a calculated detonation velocity at a density of 1.8 g cm −3 of 9037 m s −1 [5]. Graswald et al.…”
Section: Introductionmentioning
confidence: 99%